Blinatumomab treatment of older adults with relapsed/refractory B‐precursor acute lymphoblastic leukemia: Results from 2 phase 2 studies. Issue 14 (3rd May 2016) - Kantarjian, Hagop M.; Stein, Anthony S.; Bargou, Ralf C.; Grande Garcia, Carlos; Larson, Richard A.; Stelljes, Matthias; Gökbuget, Nicola; Zugmaier, Gerhard; Benjamin, Jonathan E.; Zhang, Alicia; Jia, Catherine; Topp, Max S.
Abstract : BACKGROUND: Older adults with relapsed/refractory B‐precursor acute lymphoblastic leukemia (r/r ALL) are reported to have a poor prognosis and few therapeutic options. In the current study, the authors evaluated treatment with single‐agent blinatumomab in adults aged ≥65 years with r/r ALL. METHODS: A total of 261 adults with r/r ALL who were examined across two phase 2 studies received blinatumomab in cycles of 4‐week continuous infusion and 2‐week treatment‐free intervals. The primary endpoint in each study was complete remission (CR) or CR with partial hematologic recovery (CRh) during the first 2 cycles. Data were pooled and analyzed according to patient age at screening (aged ≥65 years vs aged <65 years). RESULTS: Of 36 older adults, 56% (95% confidence interval [95% CI], 38%‐72%) achieved CR/CRh during the first 2 cycles compared with 46% (225 patients) (95% CI, 40%‐53%) of younger adults. Complete minimal residual disease responses were 60% in older and 70% in younger responders. Three older responders (15%) and 61 younger responders (59%) proceeded to allogeneic hematopoietic stem cell transplantation. Kaplan‐Meier curves overlapped for relapse‐free and overall survival for both age groups. Older adults were found to have a similar incidence of grade ≥3 adverse events (AEs) as younger adults (86% vs 80%) but more grade ≥3 neurologic events (28% vs 13%). Cytokine release syndrome occurred in 7 older (19%) (1 case of grade 3) and 23 younger (10%) (4 cases of grade ≥3) adults. There were no treatment‐related fatal AEs reported. CONCLUSIONS: Older adults with r/r ALL who were treated with single‐agent blinatumomab were found to have similar hematologic response rates and incidence of grade ≥3 AEs compared with younger adults but had more neurologic events, which were reversible and primarily resolved with treatment interruption. Cancer 2016;122:2178–85 . © 2016 American Cancer Society . Abstract : Older adults with relapsed/refractory B‐precursor acute lymphoblastic leukemia typically have a worse prognosis and fewer therapy options compared with younger patients. In this analysis of pooled data from two phase 2 studies of single‐agent blinatumomab therapy in patients with this disease, older (aged ≥65 years) and younger (aged <65 years) adults had similar treatment outcomes.